Serum irisin concentration in women with gestational diabetes. (September 2014) - Kuzmicki, Mariusz; Telejko, Beata; Lipinska, Danuta; Pliszka, Justyna; Szamatowicz, Michal; Wilk, Juliusz; Zbucka-Kretowska, Monika; Laudanski, Piotr; Kretowski, Adam; Gorska, Maria; Szamatowicz, Jacek
Abstract Irisin is a novel myokine and adipokine which induces an increase in total body energy expenditure, improving insulin sensitivity and glucose tolerance in experimental animals. In the present study, serum irisin concentration was measured by an enzyme immunoassay in 130 women with gestational diabetes mellitus (GDM) and 140 BMI-matched patients with normal glucose tolerance (NGT). Median irisin level was significantly lower in the patients with GDM than in the NGT subjects (1703.3 [1354.8–2097.9 ng/ml] versus 1873.8 [1519.8–2294.8 ng/ml], p = 0.01); however, 3 months after childbirth its concentrations did not differ markedly between the two groups (1165.9 [872.1–1497.5] ng/ml versus 1139.0 [984.0–1376.7] ng/ml). In the whole group, irisin concentration correlated negatively with 2 h glucose level (R = −0.14, p = 0.03). In the women with NGT, irisin concentration correlated positively with ISOGTT (R = 0.22, p = 0.04) and the disposition index (DI120) (R = 0.24, p = 0.03), as well as negatively with 2 h insulin level (R = −0.23, p = 0.03) and HOMA-IR (R = −0.24, p = 0.02). Multiple regression analysis revealed that 2 h glucose and DI120 were the only variables significantly influencing serum irisin (β = 0.158, p = 0.03 and β = 0.159, p = 0.02, respectively). Our results suggest that serum irisin concentration increases markedly in pregnant women, but this increase seems to be significantly lower in patients with GDM.